2004
DOI: 10.1210/jc.2003-031725
|View full text |Cite
|
Sign up to set email alerts
|

Klinefelter Syndrome in Adolescence: Onset of Puberty Is Associated with Accelerated Germ Cell Depletion

Abstract: The process of germ cell depletion in patients with Klinefelter syndrome (KS) is incompletely characterized. In the current work, we evaluated the presence of germ cells in adolescent boys with KS for possible future use in assisted reproduction techniques. Fourteen nonmosaic 47,XXY boys (aged 10-14 yr) were enrolled. Every fourth month their puberty was staged, and serum was obtained for hormone analyses. Each boy underwent a single testicular biopsy. Biopsy specimens of seven peripubertal boys (testicular vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
178
1
11

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(203 citation statements)
references
References 36 publications
13
178
1
11
Order By: Relevance
“…This finding is in contrast to other studies that report normal testicular histology and germ cell numbers during the foetal period of KS patients (Gustavson & Kjessler 1978, Flannery et al 1984. Other studies analysing testis material from the neonatal and prepubertal period have found reduced numbers of germ cells (Ferguson-Smith 1959, Mikamo et al 1968, Edlow et al 1969, Muller et al 1995, Wikstrom et al 2004. With such disparate data, it is difficult to derive any meaningful conclusions, a situation further complicated by the fact that the KS boys were partially cryptorchid, a factor known to cause a marked decrease in germ cell number independent of karyotype (Hadziselimovic & Herzog 2001).…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…This finding is in contrast to other studies that report normal testicular histology and germ cell numbers during the foetal period of KS patients (Gustavson & Kjessler 1978, Flannery et al 1984. Other studies analysing testis material from the neonatal and prepubertal period have found reduced numbers of germ cells (Ferguson-Smith 1959, Mikamo et al 1968, Edlow et al 1969, Muller et al 1995, Wikstrom et al 2004. With such disparate data, it is difficult to derive any meaningful conclusions, a situation further complicated by the fact that the KS boys were partially cryptorchid, a factor known to cause a marked decrease in germ cell number independent of karyotype (Hadziselimovic & Herzog 2001).…”
Section: Introductionmentioning
confidence: 65%
“…With such disparate data, it is difficult to derive any meaningful conclusions, a situation further complicated by the fact that the KS boys were partially cryptorchid, a factor known to cause a marked decrease in germ cell number independent of karyotype (Hadziselimovic & Herzog 2001). Wikstrom et al (2004) showed that the depletion of germ cells accelerated with increasing testosterone levels at the onset of puberty, culminating in the complete loss of germ cells. A finding that led to the proposition that meiotic failure occurring during this phase (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Wikstrom et al (17) only found germ cells in the testes of 50% of peripubertal Klinefelter boys indicating that the fertility may already be impaired at this young age. In addition, Wikstrom et al (18) showed that germ cell differentiation was arrested in spermatogonium or early spermatocyte stage in KS, and that the spermatogonia undergo apoptosis instead of entering meiosis at the onset of puberty.…”
Section: Testicular Histology In 47xxymentioning
confidence: 99%
“…Increased male age is strongly associated with a decline in male spermatogenesis. Some studies have described that age is a limiting factor for successful sperm retrieval in nonmosaic KS males and suggested that earlier infertility assessment and testicular sperm extraction in men with KS might play a critical role in their treatment (Wikstrom et al, 2004;Emre et al, 2006). Wikstrom et al (2004) found that only 50% of the boys with KS had germ cells in their testes, indicating a severely impaired fertility potential even in the peripubertal period.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have described that age is a limiting factor for successful sperm retrieval in nonmosaic KS males and suggested that earlier infertility assessment and testicular sperm extraction in men with KS might play a critical role in their treatment (Wikstrom et al, 2004;Emre et al, 2006). Wikstrom et al (2004) found that only 50% of the boys with KS had germ cells in their testes, indicating a severely impaired fertility potential even in the peripubertal period. Therefore, a potential strategy for infertility in patients with KS is cryopreservation of ejaculated spermatozoa or testicular tissue early in the patients' adolescence (Sousa et al, 2002;Ichioka et al, 2006).…”
Section: Discussionmentioning
confidence: 99%